Architecture as a Cultural Sustainability Factor of the Macedonian Cities. The Branding of Bitola. - Hristova, Aneta (NJ: Wiley, 2019)
The current need of policy programs for the Macedonian cities to reach the standards of sustainable and prosperous economic development and to enable their promotion on the European cultural map, initiated our project “Architecture as a Cultural Sustainability Factor of the Macedonian Cities”. It aims to inspect the spatial and physical potentials of the Macedonian architectural and bio-regional heritage in order to create unique and competitive brands and to develop the overall economic and touristic potentials of the Republic of Macedonia. The project encompasses cooperative agreement-based projects with the Association of the Units of Local Self-Government of the Republic of Macedonia (ZELS), counting eighty-four municipalities and the capital of Skopje as a particular self-governed unit. The National Strategy of Sustainable Development, ZELS’ “Strategic Plan 2011–2015” from 2010 and the successive municipality action plans are the basic sources of information for the investigation regarding political, architectural and social aspects for providing legal instruments and collaborative forms between the residents and the municipal governments in building up “creative class” resources for a long-term sustainable development. During the investigation we employed a wide range of methods, including collection of data and examination of archive documents, on-site surveys, mapping and evaluation of cultural and architectural heritage of the Macedonian cities and regions, interviews and collaborative meetings with municipal and civic representatives. The findings outline the general branding strategy for the Macedonian cities, adjoined with spectrum of interventions for site-specific adaptive design concepts aimed to employ their unique physical and cultural identities to brand themselves successfully. In this paper, we present our first case study, “Remediation Project for the Quay of the River Dragor”, completed in 2014 in cooperation with the Municipality of Bitola that was targeted to set the standards and the formula for the city brand success. Following the objectives of the “Strategic Plan for Local Development of the Bitola Municipality 2009–2014”, this project highlights the primacy of the environmental protection for sustainable development as the basis of the integrated design strategy that relies on ecological principles. On a political level, it pioneers the grounds on which architecture expands its disciplinary assumptions, goals, institutional, legal and financial tools in the municipal policies of sustainable development.
Keywords: architecture, cultural sustainability, cultural industries, city branding, ecological urbanism, adaptive design, participatory planning